Decision Support Analysis in Food-Borne Epidemics - Tadeusz NOWICKI; Paweł PIECZONKA; Michał SOBOLEWSKI (Communications of International Proceedings, 2023)
This paper shows the modeling and analysis of processes associated with the spread of the epidemic of food-borne diseases. The aim of this study was to show how to test the characteristics of the processes associated with the spread of the epidemic of food-borne diseases. Using formal models and methods the epidemic of food-borne diseases is investigated. The activities of sanitary inspection are considered.  It is shown how to obtain various characteristics related to operations of inspection operations during the epidemic of food-borne diseases. The result of the work are models of processes related to the activities of sanitary inspection during the epidemic of food-borne diseases. This allows analyzing the activities of sanitary inspection in preventing the spread of food-borne illness. Models are also formal description of the activities of sanitary inspection.
Keywords: epidemics of foodborne diseases; patient interviews; objects inspections; scheduling problem; cluster analysis